2010
DOI: 10.5351/ckss.2010.17.3.319
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Group Sampling Plan Based on Time-Truncated Life Tests

Abstract: In this paper, a new group sampling plan for the lot acceptance is proposed for the time truncated life test, which can be utilized when multi-item testers are implemented. The design parameters are found using the two-point approach such that the producer's and consumer's risks are satisfied simultaneously at the acceptable reliability level and the lot tolerance reliability level, respectively. The case of Weibull distribution is described to illustrate the procedure that can be used when the quality level i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…Recently, Aslam and Jun [11] developed the single-stage group acceptance plan for the inverse Rayleigh and log-logistic distribution by considering only the consumer's risk. Aslam et al [12] proposed the single-stage group acceptance plan for the gamma distribution by considering producer and consumer risks at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Aslam and Jun [11] developed the single-stage group acceptance plan for the inverse Rayleigh and log-logistic distribution by considering only the consumer's risk. Aslam et al [12] proposed the single-stage group acceptance plan for the gamma distribution by considering producer and consumer risks at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Note that g, r and c are the design parameters of the associated group acceptance sampling plan. In literature, group acceptance sampling plans have been discussed by Aslam et al (2009) for gamma distribution, Aslam and Jun (2009a) for Weibull distribution, Aslam and Jun (2009b) for inverse Rayleigh and log-logistic distributions, Rao (2010) for generalized exponential distribution and Aslam et al (2011a) for Birnbaum-Saunders distribution. It is to be noticed that two-stage group acceptance sampling plan is a further generalization of the group acceptance sampling plan.…”
Section: Introductionmentioning
confidence: 99%
“…It is to be noticed that two-stage group acceptance sampling plan is a further generalization of the group acceptance sampling plan. One may refer to the works of Aslam et al (2011Aslam et al ( ), (2011b, (2013) and cited references there-in for various results on such acceptance sampling plans.…”
Section: Introductionmentioning
confidence: 99%
“…Studies regarding truncated life tests can be found in Epstein [1], Sobel and Tischendrof [2], Goode and Kao [3], Gupta and Groll [4], Gupta [5], Fertig and Mann [6], Kantam and Rosaiah [7], Baklizi [8], Wu and Tsai [9], Rosaiah and Kantam [10], Rosaiah et al [11], Tsai and Wu [12], Balakrishnan et al [13], Srinivasa Rao et al [14], Srinivasa Rao et al [15], Aslam et al [16], and Srinivasa Rao et al [17]. All these authors designed acceptance sampling plans based on the mean life time under a truncated life test.…”
Section: Introductionmentioning
confidence: 99%